Educational Data Mining and Data Warehouse Design Using Business Intelligence (International Journal of Innovative Research in Computer Science & Technology, 2022)
Business intelligence (BI) is basically a  collection of programs, utilities and apps that allows you to  analyze large quantities of data (Big Data). Every year,  educational institutions deal with enormous amounts of Big  Data. The use of business intelligence (BI) in these  organizations is critical for improving processes and  supporting decision-making. A Datawarehouse is the  foundation of every BI project (DW). The scheme deliberations for implementing DW in any of the institutional setting are described in this article. Using  educational data mining (EDM) methods, the DW shall be  utilized in an information unearthing procedure to manage  the statistics and facts for the study of vital accomplishment metrics. A knowledge management framework's main  technical assets are a data warehouse (DW) and an  enterprise architecture (EA) repository (KMF). The agenda further was created to provide order to the processes of  knowledge generation, capture, transfer, and digitization.  This handbook and the framework are two of the results of  a private university's research effort. In addition, an illustrative example demonstrates picking of the finest  technique in higher education. The stages for DW design  are given in the case study. This research may help  academics and practitioners who want to create a data  warehouse to analyze data utilizing EDM methods.
Keywords: Business intelligence; Data Warehouse; Datawarehouse; Educational data mining; Knowledge management